2010
DOI: 10.1615/critrevimmunol.v30.i5.30
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T-cell Trafficking: From Thymic Development to Tumor-Induced Immune Suppression

Abstract: Regulatory T cells (Tregs) have become a priority for many investigators in immunology due to their potent immunosuppressive and tolerogenic effects. While Treg activity is required for normal immune homeostasis, dysregulation of their numbers can induce autoimmunity or aid in the pathogenesis of disease. Therefore, great effort has been made to understand the mechanisms by which Tregs accumulate in different areas of the body. Like other lymphocytes, Tregs migrate in response to a network of chemotactic stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 124 publications
3
54
0
1
Order By: Relevance
“…In contrast, ATP is released by tumor cells as shown in vivo (6) and in vitro (this article), and ATP stimulatory (T regs )/inhibitory (activated CD4 + cells) activity may represent a tumor-escape mechanism from the immune system. This scenario is consistent with the finding of high numbers of T regs in the cellular milieu of advanced tumors (53,54). The complex interplay between the inflammatory microenvironment, tumor cells, and effector cells of the immune system is currently investigated in our laboratory, in vivo, in animal models.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, ATP is released by tumor cells as shown in vivo (6) and in vitro (this article), and ATP stimulatory (T regs )/inhibitory (activated CD4 + cells) activity may represent a tumor-escape mechanism from the immune system. This scenario is consistent with the finding of high numbers of T regs in the cellular milieu of advanced tumors (53,54). The complex interplay between the inflammatory microenvironment, tumor cells, and effector cells of the immune system is currently investigated in our laboratory, in vivo, in animal models.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies suggested that Tregs accumulate in tumor microenvironment and suppress antitumor immune responses (4,20). In our study, we also observed that Tregs were increased in lung cancers, both in peripheral blood and MPE.…”
Section: Discussionsupporting
confidence: 84%
“…Within the tumor microenvironment, Tregs have been demonstrated to be coopted by tumor cells to escape immune surveillance (4). The increased accumulation of Tregs in tumor is associated with unfavorable prognosis in several kinds of cancers (5).…”
Section: Introductionmentioning
confidence: 99%
“…However, during the treatment period, the metastatic cancer from RCC spread, mainly to the pancreas and lungs. Generally, an immune cell-inhibiting mechanism is present in the microcirculatory environment of tumors (20). A trace number of cancer cells of RCC were latently present under the control of the immunological surveillance mechanism, but it may have manifested because the DLBCL tumor volume rapidly increased and inhibited immunity, and the subsequent growth of metastatic cancer cells from RCC may have been slightly rapid, unlike the slow growth previously reported (1,6,17).…”
Section: Discussionmentioning
confidence: 93%